Eutypellaolides A–J, Sesquiterpene diversity expansion of the polar fungus Eutypella sp. D-1 - Ning, Zhe; Hu, Bo; Sun, Yuan-Yuan; Ding, Jin-Feng; Han, Xiang-Ying; Lu, Xiao-Ling; Yin, Zi-Fei; He, Ying; Jiao, Bing-Hua; Yu, Hao-Bing; Liu, Xiao-Yu (Frontiers in Microbiology, 2024)
Eight new 12,8-eudesmanolide sesquiterpenes, eutypellaolides A-H (1-8), and two new eudesmane-type sesquiterpenes, eutypellaolides I-J (9-10), along with four known 12,8-eudesmanolide compounds 11-14, were isolated from the culture extract of the polar fungus Eutypella sp. D-1 by one strain many compounds (OSMAC) approach. The structures of these compounds were determined through comprehensive spectroscopic data and experimental and calculated ECD analysis. Antibacterial, immunosuppressive, and PTP1B inhibition activities of these compounds were evaluated. Compounds 1 and 11 exhibited strong inhibitory activities against Bacillus subtilis and Staphylococcus aureus, with each showing a MIC value of 2 µg/mL. Compound 9 displayed weak immunosuppressive activity against ConA-induced T-cell proliferation with the inhibitory rate of 61.7% at a concentration of 19.8 μM. Compounds 5, 11, and 14 exhibited weak PTP1B inhibition activities with IC50 values of 44.8, 43.2, and 49.5 μM, respectively.